The Kazan period in M.M. Agarkov's life - K.M. Arslanov; D.R. Miftakhutdinova; A.S. Pugacheva (Ученые записки Казанского университета: Серия Гуманитарные науки)
The relevance of the paper is explained by the increased interest of the scientific community in the legal heritage of Russia, including the classics of Russian civil science. The purpose of the paper is to cast light upon the Kazan period of life and creative work of Mikhail Mikhailovich Agarkov, one of the founding figures of modern legal science. Based on the analysis of archival materials, inaccuracies have been eliminated and the available data on the main events related to the Kazan period of M.M. Agarkov’s life have been specified. The facts of his educational achievements and his participation in the student meeting have been clarified. The characteristics given in the official recommendation that M.M. Agarkov could continue his work at the Department of Civil Law and Judicial Proceedings and his further trips abroad to study legal science have been described. The content of the special instruction for preparation to the examinations for getting the Master’s degree have been disclosed. It is of particular interest that M.M. Agarkov’s first publication has been found by us. This is a review of the French scientists’ works on the labor contract nature. The importance of the results obtained is that the specific archival material under analysis shows the formation of legal ideas and the scientific and pedagogical experience of civilians in the past as a component of ensuring the interrelation of traditions and innovations in the development of legal science and legal regulation.